(838) Digital Computer Systems أنظمة اجهزة الكمبيوتر (الحاسبات ) الرقمية - Farid M. Badran.. (INP, 2024)
This study is addressed to engineers and scientists who want to know about the performance of digital computers, as well as to businessmen and managers who are mainly concerned with their economic aspects. It is written primarily for non-experts to acquire a general understanding needed to effectively use the computer to solve problems in their own fields. For this purpose, main emphasis is placed on the principles and methods underlying the operation of the digital computer as a system. A detailed description of computer components may become obsolete within a few years due to rapid developments in this field.